Estudio de pre factibilidad para la instalación de una planta productora de licor de crema de papaya arequipeña (Carica pubescens) en la ciudad de Arequipa - Cerna Meléndez, Allison Athenas (2019)
The main objective of this preliminary study is to evaluate the viability of the implementation of a producing plant of the papaya arequipeña liqueur with milk cream that has as main characteristics the flavor of the fruit as well as a slight alcoholic strength.